2020
DOI: 10.4317/medoral.23737
|View full text |Cite
|
Sign up to set email alerts
|

Comparative expression of cyclooxygenase 2 and Ki67 in amelanotic and conventional oral melanomas

Abstract: Background Oral melanomas have some histopathological resemblance with its cutaneous counterpart; however, an aggressive behavior is more common in tumors that occur in the oral cavity. Several markers have been suggested as indicative of tumoral progression and aggressiveness, such as cyclooxygenase 2 (COX-2) and Ki67. Material and Methods In this study, we have compared the expression of COX-2 and Ki67 in a series of amelanotic (n=7) and melanotic oral melanomas (n=22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Although pigmentation is not fully considered a clinical/histological marker of aggressiveness, it has been reported in most species that amelanotic melanocytic tumors are often more aggressive. In 2020, Soares et al also reported that amelanotic melanomas presented a significantly higher COX-2 intensity of labelling than did conventional melanomas [ 69 ]. Such a conclusion could not be drawn in our work due to the limited number of amelanotic melanomas and the absence of clinical history.…”
Section: Discussionmentioning
confidence: 99%
“…Although pigmentation is not fully considered a clinical/histological marker of aggressiveness, it has been reported in most species that amelanotic melanocytic tumors are often more aggressive. In 2020, Soares et al also reported that amelanotic melanomas presented a significantly higher COX-2 intensity of labelling than did conventional melanomas [ 69 ]. Such a conclusion could not be drawn in our work due to the limited number of amelanotic melanomas and the absence of clinical history.…”
Section: Discussionmentioning
confidence: 99%
“… 23 The amelanotic nature of the lesion in the oral type has not been well examined. Soares et al 24 reported that elevated Ki-67 levels in non-pigmented melanomas also suggested a more aggressive condition.…”
Section: Introductionmentioning
confidence: 99%